Economic impacts of space allowance per animal on beef cattle feedlot - Lins Lima Montelli, Natalia Ludmila [UNESP]; Macitelli, Fernanda; Da Silva Braga, Janaina; Paranhos Da Costa, Mateus José Rodrigues [UNESP] (Universidade Estadual de Londrina, 2019)
The objective of this study was to assess the economic outcomes of three space allowances (6, 12, and 24 m2 per animal) for outdoor feedlots-finished beef cattle. Simulations considered confinement systems with a static capacity of 5,000 animals per cycle and two 86-day cycles per year. Performance data were obtained from 1,350 uncastrated bovine males. An increase in space allowance elevated the fixed cost per animal. Fixed and variable costs represented 3% and 93% of the total operating cost, respectively. For variable costs, around 70% was used for purchasing cattle and 17% for purchasing feed. The operating profit per animal increased as space allowance increased (R$ 80.90, R$ 102.00, and R$ 109.00 for 6, 12, and 24 m2 per animal, respectively). The three feedlot systems recovered the initial investment and had a positive net present value. In addition, the internal rates of return were 22%, 27%, and 25%, and the probabilities of financial loss were 33%, 29%, and 26% for pen sizes of 6, 12, and 24 m2 per animal, respectively. Therefore, larger space allowances improve profitability and reduce the risk of financial loss.
Keywords: Beef cattle; Finishing system; Investment analysis; Nellore; Risk analysis